2002
DOI: 10.1046/j.1365-3016.2002.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the timing of exposure to infection a major determinant of acute lymphoblastic leukaemia in Hong Kong?

Abstract: The hypothesis that protection of infants from exposure to infectious agents with delayed first exposure to one or more specific agents together contribute to the aetiology of childhood leukaemia, especially common acute lymphoblastic leukaemia (cALL), has substantial indirect support from descriptive epidemiology and case-control studies in developed Western countries. A case-control study of childhood leukaemia diagnosed at ages 2-14 years has now been conducted in Hong Kong. Cases (n=98) formed a consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 37 publications
1
63
1
7
Order By: Relevance
“…Other recent studies have ascertained infections primarily from parental recall. The majority of these studies have observed slight inverse associations between infections or specific types of infections in early life and leukaemia risk (Neglia et al, 2000;Perrillat et al, 2002;Jourdan-Da Silva et al, 2004;Ma et al, 2005), but some studies have demonstrated little evidence of an association (Schuz et al, 1999;Macarthur et al, 2008), whereas others have shown an increased risk of leukaemia after infection (Dockerty et al, 1999;Chan et al, 2002). However, parental recall of infections is open to disease-dependent recall bias and has been shown to be an unreliable measure of both the timing and occurrence of infections (McKinney et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies have ascertained infections primarily from parental recall. The majority of these studies have observed slight inverse associations between infections or specific types of infections in early life and leukaemia risk (Neglia et al, 2000;Perrillat et al, 2002;Jourdan-Da Silva et al, 2004;Ma et al, 2005), but some studies have demonstrated little evidence of an association (Schuz et al, 1999;Macarthur et al, 2008), whereas others have shown an increased risk of leukaemia after infection (Dockerty et al, 1999;Chan et al, 2002). However, parental recall of infections is open to disease-dependent recall bias and has been shown to be an unreliable measure of both the timing and occurrence of infections (McKinney et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, only one study has previously reported on ALL in relation to routinely recorded infections in early life . Other investigations of leukaemia and infections in early life (Dockerty et al, 1999;Chan et al, 2002;Perrillat et al, 2002;Jourdan-Da Silva et al, 2004;Ma et al, 2005;Macarthur et al, 2008) have primarily ascertained infection from parental recall, but this has been reported to be an inaccurate method for collecting data on childhood infections (McKinney et al, 1991). Furthermore, the parental recall of infections is open to disease-dependent bias as demonstrated by a recent study, which observed that the degree of underreporting of infections that were recorded in GP records differed in parents of children with leukaemia compared to parents of healthy children .…”
mentioning
confidence: 99%
“…[9][10][11] Greaves' hypothesized that the risks of childhood c-ALL are increased by an immune proliferative stress and this hypothesis was supported by different epidemiological studies with indications that the timing of exposure to common infections would be a major determinant to leukemogenesis process. 12,13 A review of literature demonstrated that very few data are available regarding descriptive epidemiology and biological markers of childhood leukemia in South America. However, the more recent improvement of diagnostic techniques, including immunophenotyping and molecular biology, to assist in the Brazilian groups for ALL therapeutic trials have provided complete information regarding biological characteristics of leukemia subtypes in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…These indicators are designated as "proxies" and include socioeconomic status, surgical history, allergic diseases, immunizations, attendance at daycare, breastfeeding, neonatal infections, and prenatal history, among others. [14][15][16][17][18][19][20][21][22][23][24][25] …”
Section: Measuring Exposure To Infection With Proxy Variablesmentioning
confidence: 99%
“…In a study similar to that of Chan et al, Roman et al found that exposure to fungal infections during the first year of life increases the risk of developing acute leukemia, with an OR of 1.4 (95% CI: 1.0-1.9). [14,85] …”
Section: Epidemiological Studiesmentioning
confidence: 99%